2019
DOI: 10.1634/theoncologist.2019-0552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analyses of Left- and Right-Sided Tumors in Adolescents and Young Adults with Colorectal Cancer

Abstract: Background. The incidence of colorectal cancer (CRC), particularly left-sided tumors (LT), in adolescents and young adults (AYA) is rising. Epigenetic events appear to play an important role in tumorigenesis and cancer progression, especially in younger patients. We compared molecular features of LT to right-sided tumors (RT) in AYA. Materials and Methods. A total of 246 LT and 56 RT were identified in a cohort of 612 AYA with primary CRC. Tumors were examined by next-generation sequencing (NGS), protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
(60 reference statements)
1
27
0
Order By: Relevance
“…As previously mentioned, right-sided (proximal) tumors occur predominantly in women and older patients, and are less common than left-sided distal tumors ( 23 , 24 ). Proximal tumors have higher microsatellite instability, hypermethylation and mutation burden, whereas more distal tumors are characterized by chromosomal instability ( 221 , 222 ). The burden of genetic mutations also varies between male and female CRC patients.…”
Section: Genetic Sexual Differentiation In Crcmentioning
confidence: 99%
“…As previously mentioned, right-sided (proximal) tumors occur predominantly in women and older patients, and are less common than left-sided distal tumors ( 23 , 24 ). Proximal tumors have higher microsatellite instability, hypermethylation and mutation burden, whereas more distal tumors are characterized by chromosomal instability ( 221 , 222 ). The burden of genetic mutations also varies between male and female CRC patients.…”
Section: Genetic Sexual Differentiation In Crcmentioning
confidence: 99%
“…It has been observed that CRCs found in the right side of the colon show the MSI‐high phenotype, concentrated BRAF‐RNF43 mutations, and poor prognosis due to a lack of response to standard chemotherapy and the metastatic nature of the cancer cells, whereas CRCs in the left side have a better prognosis associated with the MSS phenotype and frequent APC‐KRAS mutations. [ 91–93 ] It is known that the right side of the colon (from the duodenum to two‐third of the transverse colon) originates from the midgut during embryogenesis, whereas the left side of the colon (from one‐third of the transverse colon to the anal canal) originates from the hindgut (Figure 3). [ 94 ] These facts suggest that the difference of gene mutation subsets between BRAF‐RNF43 and APC‐KRAS may be related to the different embryonic origins of the cells in these two regions.…”
Section: Roles Of Rnf43 and Znrf3 In Tumorigenesismentioning
confidence: 99%
“…The 5-year survival rate in AYA sarcoma patients is approximately 70% [10,16], although prognoses in AYA patients may vary depending on age [16]. Our previous study showed that the 5-year survival rate of elderly sarcoma patients was 86% [17].…”
Section: Discussionmentioning
confidence: 93%